Peculiarities of political discourse in the English language - Beysembekov, Y. (KAZGUU Liberal Arts Digest Volume 1. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2021)
The question of politics has constantly been encountering heated debates. In order to fully perceive and evaluate the current political situation, the field of politics should be studied from all possible angles. This small-scale research provides a particular amount of data regarding the political discourse from a linguistic perspective. The study is devoted to examining the unit of political speech from three linguistic aspects. The collected information will lead to specific patterns and conclusions in the political discourse in the English language. To sum up, the conclusions were drawn by this study may be the foundation for other academics who are pursuing the investigation in the analogous area. Furthermore, this is the pioneering research conducted in this direction. Of course, there were other studies on political discourse, but there is no research that was held from this narrow angle. To be more accurate, this paper is the first paper to examine political discourse from three linguistic paradigms. Therefore, this discussion of peculiarities of political discourse may fill in the literature gap and contribute to enlarge the scientific database. In fact, it concluded that the main peculiarities of political discourse include being straightforward, simple, comprehensible, and audience-oriented.
Keywords: political discourse in the English language